Analisis Hasil Belajar Online Pada Materi Persamaan Keadaan Gas Ideal Siswa Sma Negeri 1 Tikke Raya Saat Wabah Covid 19 - Rahmawati, Besse; Supriyatman, Supriyatman (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
This study was conducted with the aim of analyzing online learning outcomes on the material for the Ideal Gas Equation of State 1 Tikke Raya students during the Covid 19 outbreak. The research method used in this study was a qualitative approach. The research subjects consisted of 14 students of class XI IPA 3 SMA Negeri 1 Tikke Raya. This study describes qualitatively online learning about the Ideal Gas Equation of State through the provision of tests and non-tests to students of class XI IPA 3 SMA Negeri 1 Tikke Raya. Collecting data using tests, giving non-tests and interviews. The tests used are multiple choice tests and essays that include indicators on the Ideal Gas Equation of State. Then in-depth interviews were conducted with respondents related to online learning on the ideal gas equation of state material during the Covid 19 outbreak. Based on the data, it can be found that the results of the study show that (1) the online learning outcomes of students who take online learning are more than the learning outcomes of students who participating in direct or offline learning, (2) there are several obstacles experienced by students and teachers in online teaching and learning activities, namely the addition of internet quota fees, communication and socialization between students and teachers to reduce the internet network which is less stable and adequate, and (3) This learning provides opportunities for students to study concepts in depth while at the same time improving their learning outcomes.